Evaluating the Hepatoprotective Potential of Ginger Ethanolic Extract Against Lambda-Cyhalothrin-Induced Toxicity in Male Rats - Q Mustafa, Mustafa; JM Jawad, Zainab (The Iraqi Journal of Veterinary Medicine, 2024)
Ginger (Zingiber officinale Rosc.) is a traditional plant that is widely used as a spice or folk medicine. Lambda-cyhalothrin (LCT) is a synthetic pyrethroid that is widely used to control insecticide. The present study aimed to evaluate the potential protective effect of ginger ethanolic extract (GEE) on liver toxicity experimentally induced by LCT in albino rats. The experiment involved thirty adult male rats (‎Rattus norvegicus)‎, randomly ‎allocated to ‎one of three groups (n=10/group: control group, administered distilled water orally for 12 weeks‎; ‎LCT-treated group, received 5.43 mg/kg BW ‎(1/15 LD50‎ dose calculated in this study as 81.5 mg/kg BW) orally, for 12 weeks;‎ LCT-‎GEE-treated group, received the same dose of ‎LCT along with GEE at 100 mg/kg BW orally. Body weights were ‎recorded at the start, and at ‎‎4, 8, and 12 weeks into the treatment. Upon completion of the study, blood ‎samples were collected for liver ‎enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST)‎, ‎and alkaline phosphatase (ALP) ‎assessment. Additionally, liver samples were collected for histopathological‎ ‎examination‎.‎ The LCT-treated group exhibited a significant decrease in BW at 4, 8, and 12 weeks compared to the control ‎and LCT-GEE-treated groups. The LCT-treated rats showed increased levels of liver enzymes ALP, AST, and ‎ALT. Histological evaluation revealed signs of liver necrosis, mononuclear cell infiltration, and congestion in ‎LCT-treated rats. These pathological changes were less pronounced in the LCT-GEE-treated group, indicating ‎a mitigating effect. The study demonstrates the detrimental effects of LCT on the health of male rats, ‎particularly regarding BW and liver health. Alongside, it highlights Zingiber officinale's potential in reducing ‎these adverse effects, suggesting its efficacy in environments with LCT exposure‎‎‎.